Video Catalogue Art Metropole 1985/86. (Toronto : Art Metropole, 1985)
Art Farm ; Atchley, Dana ; Birnbaum, Dara ; Blumenthal, Lyn ; Cameron, Eric ; Feingold, Ken ; Fried, Howard ; General Idea ; Graham, Dan ; Harding, Noel ; Holt, Nancy ; Hutchinson, Nora ; Kelley, Mike ; Layzell, Richard ; Levine, Les ; Muntadas, Antonio ; Odenbach, Marcel ; etc.
Table of Contents: General Information ; Artists and Works in Distribution ; Archive ; Sales and Rentals/Services ; Index/Order Form
Engels
boek